Systemic Financial Risk in Payment Systems. (IMF Working Papers; Working Paper ;, 1990)
Efficient and stable payments systems are of fundamental importance in maintaining an orderly international monetary system. Major disruptions of national and international payments systems would have highly adverse effects on international trade, capital flows, and real activity. A key issue--now being addressed by authorities in a number of major countries--is whether existing institutional arrangements need to be modified in order to reduce the liquidity and credit risks that have arisen as a result of the expansion of international capital flows and the growing integration of major financial markets. This paper examines the nature of these risks and the policies that are being implemented to manage or curb them.